Folate content of gluten-free food purchases and dietary intake are low in children with coeliac disease. (2nd October 2020) - Cyrkot, Samantha; Anders, Sven; Kamprath, Chelsea; Liu, Amanda; Mileski, Heather; Dowhaniuk, Jenna; Nasser, Roseann; Marcon, Margaret; Brill, Herbert; Turner, Justine M.; Mager, Diana R.
Abstract: The lack of mandated folate enrichment of gluten-free (GF) grains in Canada has been suspected to contribute to suboptimal folate intake among children suffering from Celiac disease (CD). Children with CD on the gluten-free diet (GFD) face nutrient imbalances (higher fat/sugar, lower folate) from processed GF foods. The study objective examined folate intake in children with CD and folate content of household food purchases. Households collected food receipts for 30 days to assess folate content. Folate-rich foods were defined as ≥60 µg dietary folate equivalent (DFE)/100g. Two 24-hour recalls assessed children's intake. Households ( n  = 73) purchased >17, 000 food items. Median child age was 10.5 y (IQR: 8.4–14.1). GF folate-rich foods represented <15% of all household food purchases and 69% of children had low folate intakes. Folate-rich foods consumed included legumes/GF-breakfast cereals. These represented 5% of GF-food purchases/intake. Few were fortified with folate. Findings highlight the need for mandated GF folate food fortification policy.